Analysis of adherence to drug use in patients with pulmonary tuberculosis on the success of therapy at the Sigli City Health Center, Pidie Regency in 2023 - Sri Handayani; Kesaktian Manurung; Johansen Hutajulu (Jurnal Info Sains : Informatika dan Sains, 2023)
Pulmonary tuberculosis is an infectious disease of the lower respiratory tract. This disease occurs due to the presence of mycobacterium tuberculosis which can be transmitted through droplets that can occur from one individual to another and form colonization in the bronchioles or alveoli. This disease if left untreated or incomplete treatment can cause dangerous complications up to death. The estimated prevalence of TB in all cases is 660,000 and the estimated incidence is 430,000 new cases per year. The number of deaths from TB is estimated at 61,000 deaths per year according to the National Strategy for Pulmonary Tuberculosis Control. What often happens that can cause failure in treatment is because the patient does not carry out instructions or in determining the right and proper treatment given by health workers to patients, it does not necessarily go well if the patient himself does not take medication properly or according to the procedure for taking the drug for pulmonary TB patients. The formulation of the problem in this study was: "Analysis of adherence to drug use in patients with pulmonary tuberculosis on the success of therapy at the Sigli City Health Center, Pidie Regency in 2023. In this study the type of research used was a descriptive analytic approach with an analytic study design using a retrospective-prospective study observations on the independent and dependent variables at the same time. The sample used in this study was a total sample or total sampling of 72 people. The results in this study obtained data namely; There is a relationship between compliance with pulmonary TB patients and the success of therapy with a ρ-value of 0.000. There is no relationship between the age of patients with pulmonary TB and the success of therapy with a ρ-value of 0.403. There is no relationship between the gender of pulmonary TB sufferers and the success of therapy with a ρ-value. 0.246, There is a relationship between the knowledge of pulmonary TB sufferers and the success of therapy with a ρvalue of 0.016. There is no relationship between the educational level of pulmonary TB sufferers and the success of therapy with a ρ-value of 0.523. There is a relationship between the work of pulmonary TB sufferers and the success of therapy with a ρ-value. 0.002 and There is a relationship between family support for pulmonary TB patients and the success of therapy with a ρ-value of 0.013. the work variable is the most significant variable related to the success of TB patient therapy at the Sigli City Health Center, Pidie Regency in 2023 (p-value 0.005 <α = 0.05) with an Ods Ratio (Exp. B) of 36.075, which means that work has success with treatment 3.6 times more compared to those who do not work.